2021
DOI: 10.3390/ijerph18073514
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Health of African Immigrant and Refugee Children

Abstract: Migration is a growing phenomenon around the world, including within the African continent. Many migrants, especially African children, face challenges related to health and social inclusion and can face increased health risks. A systematic scoping review of available literature on the health of African migrant children across the globe was conducted to offer insight into these health risks. The review was conducted over a 15-month period from January 2019 to April 2020, yielding 6602 articles once duplicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 216 publications
(351 reference statements)
2
13
0
Order By: Relevance
“…Our review thus fills a gap in knowledge by providing a comprehensive synthesis of the extant literature and outlining key findings about the physical health, mental health and social well-being of immigrant children in Canada. Our findings are consistent with recent reviews which emphasise interacting microfactors, mesofactors and macrofactors that impact the health of immigrant children in Canada 89–92. The interplay of diverse factors that improve, support or worsen the health of immigrant children stress the importance of attending to this population with multicomponent approaches that acknowledge their needs, strengths and unique experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Our review thus fills a gap in knowledge by providing a comprehensive synthesis of the extant literature and outlining key findings about the physical health, mental health and social well-being of immigrant children in Canada. Our findings are consistent with recent reviews which emphasise interacting microfactors, mesofactors and macrofactors that impact the health of immigrant children in Canada 89–92. The interplay of diverse factors that improve, support or worsen the health of immigrant children stress the importance of attending to this population with multicomponent approaches that acknowledge their needs, strengths and unique experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Lack of appropriate and adequate health information, a lack of interpreters, and poorly timed communication have been cited as barriers to contraceptive use (Gele & Harsløf, 2012). Also, the perceived high cost and perceived side effects of contraceptives may impede contraceptive utilization, leading to low use (Salami et al, 2021). Variation in sociocultural practices also makes access to family planning services challenging for African immigrants and refugees.…”
Section: African Immigrant and Refugee Populationsmentioning
confidence: 99%
“…Variation in sociocultural practices also makes access to family planning services challenging for African immigrants and refugees. Differences in religion, social norms, and the opinion of male partners were also noted as barriers to accessing family planning services (Mbanya et al, 2019; Salami et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Suglia et al (2021) observed a higher prevalence of cardiovascular risk in Hispanic/Latino and African American groups, as well as higher rates of poverty and social stress compared to the non-Hispanic population in the US [ 18 ], thus highlighting the importance of considering social factors involved in these relations. A systematic review by Salami et al (2021) analyzed migration within the African continent and found that minor African immigrants and refugees experience higher health problems linked to social factors such as lack of social inclusion or access to health care services [ 19 ]. These studies conclude, in general terms, that it is necessary to identify which psychosocial and sociodemographic factors can have an impact on immigrants’ health in order to improve programs and healthcare provided to immigrants by institutions.…”
Section: Introductionmentioning
confidence: 99%